Radiation therapy of renal cell carcinoma skeletal metastases – Does histologic subtype predict progression? - Kavin Sundaram; Joshua M. Lawrenz; Precious C. Oyem; Aditya Banerjee; Shannon Wu; Paras Shah; Shireen Parsai; Chirag Shah; Nathan W. Mesko; John Reith; Lukas M. Nystrom (Clinical Surgical Oncology)
Introduction: This investigation assessed whether the following factors were associated with radiographic local progression in bone metastases from renal cell carcinoma (RCC): (1) high-risk histologic features (2) lesional surgery (3) biologically effective dose (BED) of radiation therapy. Methods and materials: A single-institution database identified all patients who underwent surgery and radiation therapy for bone metastases from RCC to the appendicular skeleton and pelvis from 2006 to 2016. Thirty-six patients underwent radiotherapy for 80 metastases. While all patients had surgical stabilization, 17/36 also had lesional surgery to address the metastatic lesion. Progression of each individual lesion was determined using the application of RECIST criteria to imaging at last follow-up. Results: The rate of progressive disease was 8/25 (32%) in the high-risk group versus 5/55 (9%) in the standard-risk group (p ​= ​0.019). The rate of progression among high-risk metastases undergoing lesional surgery was 0/9 versus 8/16 (50%) having non-lesional surgery (p ​= ​0.0218). The rate of progression among standard-risk metastases undergoing lesional surgery was 1/16 (6%) versus 4/39 (10%) with non-lesional surgery (p ​= ​1.00). High-risk histologic features (OR: 10.592, 95% confidence interval: 1.347–83.271, p ​= ​0.025) and as well as a reduction in risk with every additional Gray of BED (OR: 0.902, 95% confidence interval: 0.827–0.984, p ​= ​0.021) were found to predict progressive disease. Conclusions: Bone metastases from renal cell carcinoma with high-risk histologic features are associated with less favorable response to radiotherapy than those with standard-risk histology. Delivery of a higher BED was associated with lower odds of progression.